LEVANTAMIENTO DE PARASITOS GASTROINTESTINALES EN OVINOS CRIADOS Y COMERCIALIZADOS EN LA MICROREGACIÓN DE CRUCERO DEL SUR, PARANÁ, BRAZIL - Esteves Bellato, Vinicius; Mataresio Antonucci, Antônio (Neotropical Helminthology, 2019)
The sheep farming mainly in the southern region of Brazil. In Paraná State the production is mainly performed in small areas with large capacity of animals, favoring the contamination of pastures and the infection of animals by gastrointestinal parasites that mostly present quickly spread. The small breeding, mostly found in this region, do not follow standards of breeding sheep, however, it was observed a higher prevalence of sheep breeding woolless, probably due to the weather favorable to the creation of these animals. In this study performed in the northwest of Paraná State, samples were randomly collected in 87 animals from five different properties. In each property was collected 30% of each category stipulated in the flock: one to three months, three to six months, six months dose, and animals over one year of age. After collecttion the feces were sent to the Laboratory of Veterinary Parasitology of UNINGA, applying method of OPG. We calculated the prevalence of identified parasites. The results demonstrated a higher prevalence (68,96%) of eggs of nematodas Strongylida type, being 60/87 parasitized animals; Strongyloides (Bavay, 1876) 25/87 samples (28,73%); Nematodiros sp. (Ransom, 1907) 6/87 (6,98%), Tricuris sp. (Ransom, 1911) 3/87 (3,44%); toxocara vitulorum (Stiles, 1905) 2/87 (2,29%); there were eggs of trematodes digenetics Dicrocolium sp. (Loos, 1907) 2/87 (2.29%), and oocysts of protozoa of the genus Eimeria sp. (Schneider, 1875) appearing on 39/87 samples (44,82%), and Cryptosporidium sp. (Tyzzer, 1907) 1/87 (1,14%). In a property was performed the autopsy of an animal, and found Oesophagostomum columbianum (Railliet & Henry, 1913), where probably the eggs Strongylidae found are due to infection by this parasite.